A practical guide to recognize, assess, treat and evaluate (RATE) primary care patients with chronic pain. Issue 3 (3rd April 2023) - Gebke, Kevin B; McCarberg, Bill; Shaw, Erik; Turk, Dennis C; Wright, Wendy L; Semel, David
ABSTRACT: The management of patients with chronic pain is one of the most important issues In medicine and public health. Chronic pain conditions cause substantial suffering for patients, their significant others and society over years and even decades and increases healthcare utilization resources including the cost of medical care, loss of productivity and provision of disability services. Primary care providers are at the frontline in the identification and management of patients with chronic pain, as the majority of patients enter the healthcare system through primary care and are managed by primary care providers. Due to the complexity of chronic pain and the range of issues involved, the accurate diagnosis of the causes of pain and the formulation of effective treatment plans presents significant challenges in the primary care setting. In this review, we use the classification of pain types based on pathophysiology as the template to guide the assessment, treatment, and monitoring of patients with chronic pain conditions. We outline key methods that can be used to efficiently and accurately diagnose the putative pathophysiological mechanisms underlying chronic pain conditions and describe how this information should be used to tailor the treatment plan to meet the patient's needs. We discuss methods to evaluate patients and the impact of treatment plans over a series of consultations, with a particular focus on strategies to improve the patient's ability to self-manage their pain and related symptoms and perform daily functions despite persistent pain. Finally, we introduce the mnemonic RATE (Recognize, Assess, Treat, and Evaluate) as a general strategy that healthcare providers can use to aid their management of patients presenting with chronic pain.